Method of calculation of geometrical parameters of building atrium structures considering the comfort of temperature and air regime - Pham Thi Hong Tham; De Tai Duong; A. K. Solovyev (Vestnik MGSU)
Introduction. The influence of atrium on temperature stratification under indoor natural ventilation of the teaching-laboratory building of the Moscow State University of Civil Engineering (MGSU) with the help of full-scale experiments is considered. Based on this, the aim of the research is to develop a new method of calculating the optimal geometric parameters of a building atrium considering the comfort of its temperature-air regime by solving the developed basic airflow equations in combination with mathematical modelling methods. The formula for determining the air flow rate for natural ventilation in atriums, analyzing and designing a natural ventilation system in a building with an atrium with more than two ventilation outlets was derived. Based on the results obtained, a conclusion is made about the optimal area of exhaust and supply openings in an atrium building at different heights. These data may have practical application in the design of buildings with atriums.Materials and methods. Semi-empirical research methods were used. Simple linear regression methods were carried out to establish a correlation between the measured variables air temperature and building construction height in an atrium with specific conditions to determine the temperature at any height.Results. The formula for calculating the optimal area of inlet and outlet openings in connection with the atrium height and their influence on the thermal characteristics of the structures of buildings with atriums was developed.Conclusions. The results of the research make it possible to quickly and accurately determine the geometric parameters to ensure the reduction of air temperature in buildings with atriums. This plays an important role in the initial design phase.